Structural versatility of six transition metal complexes based on M(II)(2, 2′-biimidazole) building blocks and co-ligands. (9th March 2015) - Liu, Min; Yang, Yu-Ping; Yang, Yong-Sheng; Qiu, Qi-Ming; Jin, Qiong-Hua; Meng, Qing-Xuan; Chen, Hua; Yang, Wei; Dai, Yong-Cheng; Xu, Li-Jun
Graphical abstract: The crystal packing of all six complexes shows that cationic M(II)(2, 2′-biimidazole) fragments are self-assembled to construct the 3D supramolecular networks by hydrogen bonding and π–π interactions. The choice of inorganic counter anions and co-ligands has great influence on the experimental productions. Abstract: Reaction of transition metal(II) salts with 2, 2′-biimidazole (H2 biim) and co-ligands formed a series of new complexes, [M(H2 biim)2 (bipy)2 ](NO3 )2 ·2H2 O (1 –3 ) (M = Co, Ni, Zn), [Co(H2 biim)2 (bipy)](ClO4 )2 ·3H2 O (4 ), [Cu(H2 biim)2 ]3 (μ-C3 H3 O4 )2 (C3 H2 O4 )2 ·6H2 O (5 ), [Co(H2 biim)2 (H2 O)2 ](C3 H3 O4 )2 (6 ) (bipy = 4, 4′-bipyridine, C3 H2 O4 = malonate dianion, C3 H3 O4 = malonate anion). These complexes were characterized by single-crystal X-ray diffraction, and elemental analysis. All complexes except4 were also characterized by luminescence spectra and thermogravimetric analysis. The crystal packing of these six complexes shows that cationic M(II)(2, 2′-biimidazole) fragments are self-assembled to construct the 3D supramolecular networks by hydrogen bonding and π–π interactions. The 3D supramolecular networks are significantly affected by counter anion and co-ligands. In complexes1 –3, there are two sets of (4, 4) nets which pass through each other to form inclined 2D interpenetration. Complex4 is obtained by similar reactions as1 Compared with1, the only difference in4 with the reactant Co(NO3 )2 ·6H2 O replaced by Co(ClO4 )2 ·6H2 O, but it has a very different structure. In 4, the 3D networks containing cavities of 23 × 23 Å is formed. In complex5, the uncoordinated waters form an infinite 1D pipe structure which is embedded in the 3D porous network. The acid–water ring and R2 2 (9) synthons in complex6 lead to the formation of (4, 4) 2D network.